Spatial Temporal Analysis of Extreme Rainfall Using Satellite Rainfall in the Barito Watershed - Bees, Azarya; Sri Santi L M F Seran; Krisantos Ria Bela (Journal of Civil Engineering and Planning (JCEP), 2024)
The Barito watershed, as one of the largest watersheds on the island of Kalimantan, has an upstream area that is close to the equator, while the downstream area is far from the equator. This makes it interesting to see climate variability, especially rainfall that occurs in the Barito watershed. The extreme rainfall indices R20mm and R50mm are used to see the spatial variability of rainfall events, while R1X and RX5 are used to see the temporal variability of rainfall that occurs in the Barito watershed. This research shows that the frequency of rainfall events from meteorological stations, PERSIANN satellites and GPM satellites occurs most frequently in the Upper Watershed area. However, rainfall trends have not shown significant results in the last 21 years between the upstream, middle and downstream watershed areas. This is influenced by the sloping and flat conditions of the watershed, resulting in rainfall intensity tending to occur evenly throughout the watershed. The results of the IDF analysis show that there are similarities between the rainfall intensity measured at the meteorological station and the PERSIANN satellite, which gives varying intensity values ​​over a short duration of less than 50 minutes.